2013
DOI: 10.1242/bio.20136080
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle dependent localization of MELK and its new partner RACK1 in epithelial versus mesenchyme-like cells in Xenopus embryo

Abstract: SummaryMaternal Embryonic Leucine zipper Kinase (MELK) was recently shown to be involved in cell division of Xenopus embryo epithelial cells. The cytokinetic furrow of these cells ingresses asymmetrically and is developmentally regulated. Two subpopulations of xMELK, the mMELK (for “mitotic” xMELK) and iMELK (“interphase” xMELK), which differ in their spatial and temporal regulation, are detected in Xenopus embryo. How cells regulate these two xMELK populations is unknown. In this study we show that, in epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…2006 ), we first monitored MELK-GFP localization throughout the cell cycle by time-lapse imaging. We found, in agreement with other studies ( Chartrain et al 2006 , 2013 ; Tipton et al 2012 ), that MELK localizes to the mitotic cleavage furrow during cytokinesis in RPE1 cells ( Figure 2C ). We therefore next introduced the live-cell nuclear stain SiR-DNA (Spirochrome) into doxycycline-inducible MELK-GFP RPE1 cells to label the chromatin and used time-lapse imaging microscopy to investigate the effect of MELK-GFP overexpression in mitosis.…”
Section: Resultssupporting
confidence: 93%
“…2006 ), we first monitored MELK-GFP localization throughout the cell cycle by time-lapse imaging. We found, in agreement with other studies ( Chartrain et al 2006 , 2013 ; Tipton et al 2012 ), that MELK localizes to the mitotic cleavage furrow during cytokinesis in RPE1 cells ( Figure 2C ). We therefore next introduced the live-cell nuclear stain SiR-DNA (Spirochrome) into doxycycline-inducible MELK-GFP RPE1 cells to label the chromatin and used time-lapse imaging microscopy to investigate the effect of MELK-GFP overexpression in mitosis.…”
Section: Resultssupporting
confidence: 93%
“…As MELK was previously shown to be involved in cytokinesis in Xenopus embryos [20] and mammalian cells [21], we first monitored MELK-GFP localization throughout the cell cycle by time-lapse imaging. We found, in agreement with other studies [39][40][41], that MELK localizes to the mitotic cleavage furrow during cytokinesis in RPE1 cells (Fig. 2C).…”
Section: Altered Expression Of Melk Does Not Impair Mitotic Fidelity In Mammalian Cellssupporting
confidence: 94%
“… 5 Numerous studies have demonstrated that MELK is a cell-cycle modulator essential for mitotic progression. 6 , 7 Moreover, MELK also participates in other important processes, such as stem cell self-renewal, 8 , 9 and apoptosis inhibition. 10 , 11 Furthermore, MELK is overexpressed in various cancers and high expression of MELK is related with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%